Study of neurological deficits in patients with tuberculous meningitis and its association with urodynamic study - Gupta, Arvind; Garg, R. K.; Gupta, Sandhya (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculous meningitis (TBM) is the main form of tuberculosis that affects the central nervous system and is associated with high rates of death and disability. The objective of this study was to study neurological symptoms in TBM patients using clinical diagnosis and MRI of spine and comparing with urodynamic study. Methods: Fifty one patients diagnosed with TBM were studied in Neurology Department of KGM Medical University, Lucknow. Uroflowmetry and urodynamic study were done to divide the patients into normal and abnormal. A detailed history taking, general physical and neurological examination using MRI spinal cord was done and recorded on a predesigned proforma. Results: Visual impairment, hemiparesis, paraparesis, abnormal tone and reflexes in lower limbs showed significant association with abnormality in urodynamic study. MRI spine showed significant relationship of spinal meningeal enhancement, lumbosacral arachnoiditis, with abnormal urodynamic study. Conclusions: We found a significant association between neurological symptoms and abnormal urodynamic